2005
DOI: 10.1002/ijc.21276
|View full text |Cite
|
Sign up to set email alerts
|

Ribozyme‐targeting reveals the rate‐limiting role of pleiotrophin in glioblastoma

Abstract: Glioblastomas (GBMs) are the most frequent malignant brain tumors with very limited treatment options and nearly all GBM patients dying within 1 year. Pleiotrophin (PTN, HB-GAM, HBNF, OSF-1) is a secreted growth factor that shows mitogenic, chemotactic and transforming activity. While PTN expression is tightly regulated during embryogenesis and very limited in normal adult tissues, a marked PTN upregulation is seen in tumors including glioblastomas. Targeting of the PTN receptors, ALK and RPTP-zeta, indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
12

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 41 publications
2
31
0
12
Order By: Relevance
“…These findings confirmed in vivo that the peptide HARPΔ111-136 sensitized U87MG cells to apoptosis. Discussion HARP has been described as a growth factor for several tumor types (3,15,33) and in a previous study using U87MG glioblastoma cell line as an experimental model, we demonstrated that the HARP inhibitor HARPΔ111-136 exerts antiproliferative and potent anti-angiogenic activities. The aim of the present study was to investigate the mechanism of HARPΔ111-136 biological action; a recombinant adenovirus was used to produce high levels of the inhibitor HARPΔ111-136 in the glioblastoma U87MG cell line.…”
Section: The Combination Of Rt and Ad-harpδ111-136 Treatments Reducessupporting
confidence: 56%
See 1 more Smart Citation
“…These findings confirmed in vivo that the peptide HARPΔ111-136 sensitized U87MG cells to apoptosis. Discussion HARP has been described as a growth factor for several tumor types (3,15,33) and in a previous study using U87MG glioblastoma cell line as an experimental model, we demonstrated that the HARP inhibitor HARPΔ111-136 exerts antiproliferative and potent anti-angiogenic activities. The aim of the present study was to investigate the mechanism of HARPΔ111-136 biological action; a recombinant adenovirus was used to produce high levels of the inhibitor HARPΔ111-136 in the glioblastoma U87MG cell line.…”
Section: The Combination Of Rt and Ad-harpδ111-136 Treatments Reducessupporting
confidence: 56%
“…Resistance to apoptosis is a well known feature of glioblastoma cells leading to a poor response to chemotherapy and radiation therapy (14). Since HARP has been considered as a growth and a survival factor for cancer cells (15,16), blocking the HARP pathway could be of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…Of critical importance, different approaches to attenuate PTN's function in the tumor cells that in appropriately express Ptn was found to decrease tumor growth in vivo, thus constitutive PTN signaling is vital and a rate-limiting factor in the pathogenesis of these tumors. [50][51][52][53] …”
Section: Pleiotrophin and Cancermentioning
confidence: 99%
“…ALK receptor expression, originally documented in a variety of cancer lines, has been documented in many neuronal tumors , Miyake et al 2002, Stoica et al 2002, Osajima-Hakomori et al 2005, glioblastoma (Powers et al 2002, Shao et al 2002, Grzelinski et al 2005, Lu et al 2005, and mesenchymal neoplasms including melanoma (Dirks et al 2002) and rhabdomyosarcoma (Morris et al 1994, Falini et al 1998, Cessna et al 2002, Pillay et al 2002, Li et al 2004. In this context, ALK overexpression or gain of function mutations have been demonstrated to be tumorigenic.…”
Section: Introductionmentioning
confidence: 99%